A 52‐week prophylactic randomised control trial of omega‐3 polyunsaturated fatty acids in bipolar disorder. (10th January 2021) - McPhilemy, Genevieve; Byrne, Fintan; Waldron, Mairead; Hibbeln, Joseph R.; Davis, John; McDonald, Colm; Hallahan, Brian
Abstract: OBJECTIVES: Previous work suggests supplementation with omega‐3 polyunsaturated fatty acids (PUFAs) may improve mood symptoms in bipolar disorder (BD) although findings remain unclear. In this study, we assess the efficacy of omega‐3 PUFA administration for prophylaxis in BD using a clinical trial design over 52‐weeks (ClinicalTrials.gov Identifier: NCT04210804). METHODS: Individuals with BD (n = 80) were randomised to receive placebo (n = 40) or 1 g eicosapentaenoic acid (EPA) plus 1 g docosahexaenoic acid (DHA; n = 40) adjunctively for 52‐weeks. The primary outcome measure comprised the number of mood episode relapses including hospital admissions and medication changes experienced. Secondary outcome measures included time to first mood episode relapse and change in psychometric measures of depression and elation (Hamilton Depression Rating Scale and Young Mania Rating Scale). RESULTS: No significant differences in the number of mood episode relapses ( U = 490.00, p = 0.14) or the number of individuals requiring admission to hospital ( χ 2 = 0.67, p = 0.41) or medication adjustment in the omega‐3 PUFA compared to the placebo group were noted. Time to relapse was not significantly different between groups (Log Rank χ 2 = 0.41, p = 0.52). Change in Young Manic Rating Scale ( F (3.12, 152.86) = 2.71, p = 0.05) was significantly different between treatment groups over 12‐months, with scores at 9‐months and 12‐months significantly lower than those at 3‐months in the omega‐3 group and not in the placebo group. Change in Hamilton Depression Rating Scale, Global Clinical Impression and Global Assessment of Functioning were not different between groups. CONCLUSIONS: Despite a minor reduction in hypomania scores in the omega‐3 PUFA group compared to placebo, we find little evidence that the supplementation of omega‐3‐PUFAs exhibits prophylactic benefit in BD.